Distribution of Trichogramma (Trichogramma) Species in Tugai Forest Conditions and their Practical Significance - Allayarova, Madina (American Journal of Biology and Natural Sciences, 2026)
This study investigates the distribution, population characteristics, and practical significance of parasitoid insects of the genus Trichogramma in tugai forest ecosystems. The main objective of the research is to determine the species diversity, occurrence frequency, and seasonal dynamics of Trichogramma species under tugai forest conditions, and to provide a scientific justification for their role in the natural regulation of pest insect populations. The research methodology was based on an integrated approach combining field and laboratory studies. Field surveys were conducted in Tugai forest sites located along river valleys. Eggs of pest Lepidoptera were collected from various host plants, and the degree of parasitism by Trichogramma species was assessed under laboratory conditions. Species identification was performed based on morphological characteristics, and the obtained data were processed using statistical analysis methods.